Hybrid Spirituality in Paulo Coelho’s Novel Al-Khīmiyāī: A Study of Lucien Goldmann’s Genetic Structuralism - Sarah Khairunnisa Arifin; Rohanda; Mawardi (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
The objective of this research is to reveal how hybrid spirituality is constructed in Paulo Coelho’s novel Al-Khīmiyā’ī using Lucien Goldmann’s Genetic Structuralism. This study employs a qualitative descriptive method. Data were collected by identifying textual units, including narratives and dialogues, that represent the interaction between Western and Eastern values. The analysis was conducted by connecting the internal structure of the story with the broader social context of the author to reach a comprehensive understanding of the text. The results indicate that the protagonist, Santiago, successfully harmonizes individual agency (the West) with spiritual surrender or maktub (the East). Paulo Coelho is identified as a representation of the collective subject of modern society seeking common ground amidst the spiritual crisis of the global era. This research concludes that the novel offers a Hybrid Spirituality as a solution to value contradictions between cultures, affirming the role of literature as a bridge for global harmony.